Comment comprendre les « communs » : Elinor Ostrom, la propriété et la nouvelle économie institutionnelle - Olivier Weinstein (Revue de la Régulation)
The purpose of this paper is to examine the institutional theory of Elinor Ostrom, in its relations to the “new institutional economics”, and more particularly the analyzes which, following the Coase paper on social costs, gives a special place to the question of ownership. This will allow us to highlight key aspects of the theorization of Elinor Ostrom, and the issues they raise. We proceed in three steps. We first evoke the main theoretical references that are the basis of her analysis of Common Pool Resources, and mark some of her theoretical orientations. We then goes on to explore the key features of Elinor Ostrom’s institutionalism, confronted with the new institutionalism. To do this, we first consider her original and important analysis of rules and norms, and its conception of economic behavior, then we explore her theory of property rights and of the conditions of selection of forms of property and institutions, with the prospect of a confrontation with the idea of a “generalized Coase theorem”. This leads us, finally, to questioning Elinor Ostrom’s views on institutions and the commons, and possible ways to go beyond these conceptions.